Feasibility Study of Border Industrial Town Using AHP and TOPSIS - Ebrahim Fataei (جغرافیا و توسعه, 2014)
Ardabil province can be evaluated in terms of creating a boundary industrial zone to cause being in border area, neighbouring with the Republic of Azerbaijan and the customs and export to various countries. Feasibility of establishing boundary industrial estate is affected by factors such as population growth, employment, land constraints, industrial development, the customs Border, environmental protection and development, land use, raw material supply and etc. Multi-criteria decision-making methods as science, technology, management and analysis of data, can solve the problems relative to the site selection of boundary industrial estates. Various methods and algorithms for site selection have been used by researchers. This study was performed to select the appropriate location for the construction of boundary industrial estate in Ardabil Province. To achieve this objective, environmental, economic and social characteristic by AHP and TOPSIS methods was used for feasibility boundary industrial estate. Various criteria such as climate, landform, land use, protected areas, roads and highways, infrastructure, industrial development, unemployed people, exist primary sources were used. After performing calculations and algorithms, the results showed that use of two methods for locating industrial zone boundary did not have significant difference. As In both methods, the Namin city was determined ideal place for building boundary industrial estate.